ANALISA PENCAPAIAN HEALTH SAFETY ENVIRONMENT (HSE) PERFORMANCE INDICATOR PADA KONTRAKTOR BERDASARKAN CONTRACTOR SAFETY MANAGEMENT SYSTEM (CSMS) PT. X PURWOKERTO - Dwi Arita 'Afianiyah; Hanifa Maher Denny; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Contractor Safety Management System (CSMS) is an aspect of Occupational Health and Safety (OHS) management system for contractors’ work. CSMS application level can be seen through the percentage achievement of Health Safety Environment (HSE) Performance Indicator. HSE Performance Indicator can be used to monitor safety performance by looking at lagging and leading indicators. The absence of measurement HSE Performance Indicator contractors of PT. X can cause a lack of discipline OHS program implementation contractors for execute their work. This study aims to determine the achievement of HSE Performance Indicator contractor PT. X uses a qualitative method by conducting in-depth interviews. The subjects of this study consisted of two main informants and two informants triangulation. The results showed that the implementation of CSMS in PT. X consist of the step of administration which includes risk assessment, pre-qualification, and selection and implementation phase of work includes pre-implementation and implementation activities. While the achievement of HSE Performance Indicator contractors with high risk occupations amounted to 27.33%, the achievement of HSE Performance Indicator contractor to work as medium risk amounted to 13.83%, and the achievement of HSE Performance Indicator contractors with a low risk occupations amounted to 28.08%. Achievement of HSE Performance Indicator is strongly influenced by the implementation of CSMS stages. PT. X needs to do more rigorous screening to select a contractor who truly realize the importance of the implementation of OHS during works, in addition to the need for closer scrutiny of the implementation of OHS program contractors during the execution of a work in progress.